An efficient finite element model for buckling analysis of grid stiffened laminated composite plates. (April 2015) - Huang, Liang; Sheikh, Abdul H.; Ng, Ching-Tai; Griffith, Michael C.
Abstract: For the prediction of buckling response of grid stiffened composite panels having different stiffening arrangements, an efficient finite element modelling technique is presented. The laminated skin of the stiffened structure is modelled with a triangular degenerated curved shell element. An efficient curved beam element compatible with the shell element is developed for the modelling of stiffeners which may have different lamination schemes. The deformation of the degenerated beam element is completely defined in terms of the degrees of freedom of shell elements and it does not require any additional degrees of freedom. This modelling strategy has helped to reduce the number of unknowns significantly compared to the usual approach where solid or shell elements are used for modelling stiffeners. As the usual formulation of degenerated beam elements overestimates their torsional rigidity, a torsion correction factor is introduced for different lamination schemes. Numerical examples are solved by the proposed finite element technique to assess its performance and it shows that the accuracy of the proposed model is quite satisfactory. A parametric study is presented to show the effects of skin thickness, stiffener breadth and stiffener depth on the buckling capacity of grid stiffened composite plates.